Geochemical investigation of basalts from Trois Menestrels, Kerguelen Archipelago - Diop, Habib Elhadji Sy (Kansas State University, 2008)
The Kerguelen Archipelago and the submarine Northern Kerguelen Plateau consist primarily of basalt erupted by the intraplate Kerguelen hotspot. The exposed volcanic rocks are tholeiitic basalts (29 Ma) followed by lesser alkalic basalts, highly alkaline phonolites, and syenites (24 Ma). This study presents the mineralogy, isotopic and geochemical compositions of lavas (n=59) from a 650 m section exposed in the wall of a glacial valley at Trois Menestrels in the Kerguelen Archipelago. This basalt section, exposed south of the Cook Ice Cap and closest to the Raillier du Baty alkalic plutonic complex, is further south and west of previously studied basalts exposed on the Plateau Central. Results of 40Ar/39Ar dating show the Trois Menestrels lavas erupted approximately 25 Ma, approximately contemporaneously with other Plateau Central lavas and thus provide an opportunity to examine spatial compositional variations within the Kerguelen hotspot. Though the Trois Menestrels lavas are tholeiitic, The samples plot on the tholeiitic field at the stratigraphic section of Trois Menestrels, 80% of lavas from Mt. Tourmente are transitional to alkalic in the younger rocks (25.6 Ma). This sequence of tholeiitic to transitional to alkalic compositions is mirrored at Mt. Capitole and Mt. Marion Dufresne. Sr, Ba, Pb, Nb, Zr versus Nb plots show similar patterns across the Plateau Central and abundances overlap within error. Variations in isotopic composition reveal that Trois Menestrels is rather homogeneous compared to the other sections. A fundamental issue that derives from these results is the close relationship between these different rocks of the various region of the Plateau Central.
Keywords: Kerguelen archipelago; Trois Menestrels; Tholeiitic basalts; Kerguelen hotspot; Indian Ocean; Plume heterogeneity; Geochemistry (0996); Geology (0372)